Proximate foreigners : England and its neighbors in the history plays of the 1590s - De Young, Erin Marie (Trinity College (Dublin, Ireland). School of English, 2014)
The central claim of this thesis is that the correlation between the rise history play genre in the 1590s, concerns about national identity, and emerging disputes over expansion collided in the political/cultural views of proximal foreigners. By looking at those peoples with whom the English had continual exchange due to their geographic proximity, this study posits that these relationships were the ones which shaped English identity and English policy. The varying natures of the relationships between the English, Welsh, Irish, Scottish, and French all contribute varying facets to the emerging and expanding nation.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin